Pengaruh Rasio Likuiditas, Solvabilitas dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Indeks LQ45 - Auliffi Ermian Challen; Elmanizar Elmanizar; Erina Amarvia Yunazar (Journal of Accounting, Management, and Economics Research (JAMER), 2023)
This study aims to analyze the effect of liquidity ratios, solvency ratios, and profitability ratios on stock prices. This study uses a sample of companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The analysis technique used is multiple linear regression analysis. Testing the hypothesis used is a partial statistical test (t-test) with the test results showing that only the solvency ratio variable has a negative effect on stock prices and the profitability ratio has a positive effect on stock prices. While the variable liquidity ratio has no effect on stock prices.